Influence of Cement Type and Water-to-Cement Ratio on the Formation of Thaumasite - Ailian Zhang; Linchun Zhang (Advances in Materials Science and Engineering)
Cement mortar prisms were prepared with three different cement types and different water-to-cement ratios plus 30% mass of limestone filler. After 28 days of curing in water at room temperature, these samples were submerged in 2% magnesium sulfate solution at 5°C and the visual appearance and strength development for every mortar were measured at intervals up to 1 year. Samples selected from the surface of prisms after 1-year immersion were examined by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The results show that mortars with sulfate resisting Portland cement (SRC) or sulphoaluminate cement (SAC) underwent weaker degradation due to the thaumasite form of sulfate attack than mortars with ordinary Portland cement (OPC). A lower water-to-cement ratio leads to better resistance to the thaumasite form of sulfate attack of the cement mortar. A great deal of thaumasite or thaumasite-containing materials formed in the OPC mortar, and a trace of thaumasite can also be detected in SRC and SAC mortars. Therefore, the thaumasite form of sulfate attack can be alleviated but cannot be avoided by the use of SAC or SRC.